The Effect of Neuromuscular Training on Mental Health, Depression, and Quality of Life among Older Women: A Randomized Controlled Trial - Ghayour Najafabadi, Mahboubeh; Rahmani, Pooneh; Gharayagh Zandi, Hassan; Nasiri, Ali; Pourreza, Amir; Kelly dos Santos, Isis (Health Nexus, 2026)
The rapid growth of the global aging population has intensified concerns regarding the physical, psychological, and social well-being of older adults, particularly women, as age-related declines in neuromuscular control, balance, and mental health contribute substantially to reduced functional independence and quality of life. Neuromuscular training (NMT) has emerged as a promising multimodal approach to counteract these effects. This study aimed to evaluate the impact of a structured six-week NMT program on mental health, depression, and quality of life in older women. This quasi-experimental study employed a pretest–posttest design with a control group. Thirty women aged 60–70 years were randomly assigned to either an experimental group (n=15) or a control group (n=15). The experimental group participated in an 18-session NMT program over six weeks, while the control group maintained their usual activities. Mental health, depression, and quality of life were measured using the GHQ-28, Beck Depression Inventory-II, and WHOQOL-BREF questionnaires, respectively. Data were analyzed using analysis of covariance (ANCOVA) in SPSS26, with the level of statistical significance set at P<0.05. Preliminary analyses confirmed baseline equivalence between groups (p>0.05), and all ANCOVA assumptions were met. After the intervention, NMT produced significant improvements in mental health (F (1, 27) =7.93, p<0.001, η²=0.38), depression (F (1, 27) =2.29, p=0.004, η²=0.27), and quality of life (F (1, 27) =10.26, p=0.001, η²=0.32). These findings indicate that NMT accounted for a substantial proportion of variance in the measured outcomes. Neuromuscular training significantly improved mental health and quality of life while reducing depressive symptoms among older women. As a safe, low-cost, and accessible form of exercise, NMT may serve as an effective strategy to promote psychological well-being and healthy aging in this population.